Application Prospect of Quantum Communication Technology in Uav Field - He, Qun (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of quantum technology, quantum communication technology, as its core component, is gradually infiltrating into the field of UAV, which has brought revolutionary improvements to the security, communication performance and task execution ability of UAV. This paper aims to explore the application prospect of quantum communication technology in the field of UAV, analyze its impact on the performance of UAV system, and look forward to the future development direction. Through theoretical analysis and case study, this paper reveals the great potential of quantum communication technology in improving UAV combat effectiveness, ensuring information security and promoting industry innovation.